Implementation of Smart Contracts Ethereum Blockchain in Web-Based Electronic Voting (e-voting) - Susanto, Ajib (Jurnal Transformatika, 2020)
The increasing of digital technology today has helped many people to fulfill their needs. But the election system, still conventionally using paper in its implementation. Elections in general still use a centralized system, where there is an organization that manages it. Some of the problems that may occur in traditional electoral systems are that there are organizations that have full control over the database and system, so the possibility of hacking the database is quite a big opportunity.Blockchain innovation is one arrangement that can be utilized in light of the fact that it has a decentralized framework and the whole database is duplicated by all clients. Blockchain itself has been used by Bitcoin and Ethereum cryptocurrency which is known as a decentralized system. By using the blockchain in database recording on an e-voting system can reduce one source of fraud that is database manipulation. This study discusses the recording of voting data using blockchain technology. The implementation of Smart Contracts contained in the Ethereum Blockchain will be implemented to create this voting system
Keywords: Blockchain; Ethereum; Smart Contracts; Voting; E-voting